Potential benefits of oral administration of AMORPHOPHALLUS KONJAC glycosylceramides on skin health - a randomized clinical study - Sudeep Heggar Venkataramana; Naveen Puttaswamy; Shyamprasad Kodimule (BMC, 2020)
Abstract Background Ceramides play a fundamental role in maintaining the skin health as a function of improved barrier permeability. Reduced ceramide content results in skin dryness and wrinkledness. Intake of dietary ceramides potentially compensates the skin ceramide content. In the present study we have assessed the skin health benefits of oral supplementation of a hydroalcoholic extract from Amorphophallus konjac tubers standardized to 5% glycosylceramides, in a placebo-controlled clinical trial. Methods Fifty-one healthy human volunteers (aged 18-60 years) were supplemented with 100 mg/day of either a placebo or A. konjac extract capsules (5 mg glycosylceramides) for 6-weeks. The skin parameters were evaluated through dermatological diagnosis. Subject perceived efficacy of the product was further evaluated by a self-assessment questionnaire. Results Oral intake of A. konjac extract significantly decreased the skin dryness, hyperpigmentation, redness, itching and oilyness (p < 0.05). The improvement in skin health following intake of A. konjac extract was observed to be time-dependent from the start. Further, A. konjac extract was well-tolerated throughout the study, as no adverse events or toxic changes were recorded. Conclusion The study demonstrates the skincare properties of orally ingested glycosyl ceramides from konjac tubers. Trial registration CTRI/2018/12/016661 dated 13/12/2018 retrospectively registered, http://ctri.nic.in/Clinicaltrials/showallp.php?mid1=19851&EncHid=&userName=SkinCera